The lived experiences of late-adolescent female suicide survivors: 'A part of me died' - Willem A. Hoffmann; Chris Myburgh; Marie Poggenpoel (AOSIS, 2010)
People's thoughts often focus on the suicide victim immediately after a completed suicide. Yet, the real victims of such an event are those individuals who are left behind to cope with the aftermath of the suicide. This phenomenological psychological study explored the lived experiences of late-adolescent suicide survivors, particularly those negative experiences that seemed to worsen in the weeks and months after a significant other's completed suicide. The research participants were five female late-adolescents (aged 17-22 years) who were recruited by means of purposive sampling at a South African tertiary institution and at youth camps. Data collection consisted of collage-facilitated, face-to-face phenomenological interviews. In addition, some participants provided documentary material in the form of personal diaries, letters and poems. The data analysis was conducted according to Giorgi's phenomenological method. The following salient experiences emerged during the data analysis: guilt, self-blame, blaming others or God, anger, loss or restriction of 'self', depression, suboptimal behavioural coping patterns, changes in relationship dynamics, and suicidality. The results of this study can be used by mental health professionals and caregivers to support adolescent suicide survivors effectively, in the midst of their mourning. Opsomming Mense se gedagtes fokus meestal op die selfmoordslagoffer onmiddellik na 'n voltooide selfmoord. Tog is die werklike slagoffers die persone wat agterbly om die lewe na die selfmoord te hanteer. Hierdie fenomenologies-sielkundige studie het die geleefde belewenisse van laat-adolessente oorlewendes ondersoek, spesifiek daardie negatiewe belewenisse wat skynbaar erger word in die weke en maande na 'n betekenisvolle ander se voltooide selfmoord. Die navorsingsdeelnemers was vyf vroulike laat-adolessente (17-22 jaar oud) wat gewerf is deur middel van doelgerigte selektering by 'n Suid-Afrikaanse tersiêre instelling en jeugkampe. Data-insameling het geskied aan die hand van collage-gefasiliteerde, aangesig-tot-aangesig fenomenologiese onderhoude. Sommige deelnemers het addisionele dokumente in die vorm van persoonlike dagboeke, briewe en gedigte beskikbaar gestel vir data-analise. Die data is geanaliseer volgens Giorgi se fenomenologiese metode. Die volgende belewenisse het na vore getree tydens die data-analise: skuldgevoelens, self-blaam/spyt, blameer ander/God, woede, verlies/inperking van 'self', depressie, sub-optimale gedragshanteringspatrone, veranderinge in verhoudingsdinamika, en selfmoordneigings. Die resultate van hierdie studie kan deur geestesgesondheidwerkers en versorgers aangewend word om adolessente selfmoordagtergeblewenes effektief te ondersteun in die rouproses.